Strategi Penyusunan Silabus Pembelajaran Bahasa Arab Berbasis Pendekatan Komunikatif - Mahyudin Ritonga; Amiratun Nisak; Fadhilah El-Wahdah Harahap; Felzi Rehanda (IAI Muhammadiyah Sinjai, 2023)
A communicative syllabus is a syllabus that is prepared to emphasize communicative abilities in learning Arabic. This communicative syllabus places more emphasis on learning Arabic as a means of communication rather than mastering Arabic language rules. This research uses a qualitative approach. This approach is used because the data types and data types are in accordance with what is needed. This type of research is a literature review. Based on the findings obtained that the communicative syllabus model can be realized in teaching and learning Arabic, this communicative syllabus places more emphasis on learning Arabic as a communication tool rather than mastering Arabic language rules. The communicative syllabus is more appropriate to apply in classes where students have a target language background who are able to communicate. Meanwhile, for beginner classes, this syllabus is not appropriate to apply because students have not yet mastered the required language components.